Pengaruh Kepercayaan, Orientasi Belanja dan Kualitas Layanan Elektronik Terhadap Keputusan Pembelian Produk Fashion di Online Shopping (Studi Kasus pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Mulawarman) - Tri Utami Pangestu; Rahmawati Rahmawati; Asnawati Asnawati (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
This research aims to determine the influence of Trust, Shopping Orientation and Quality Of Electronic Service On purchasing decisions fashion product in online shopping (A case Study Students Economic and Business Faculty of Mulawarman University). Sampling in this research using of non probability sampling. The sample used is all students Economic and Business of Mulawarman University. The number of sample used is 100 respondents. Data analysis method used is Multiple Linier Regression using SPSS version 23. The result of this study indicate that the variables of Trust, Shopping Orientation and Quality Of Electronic Service have a significant positive effect on purchasing decisions fashion product in online shopping.